Freedom of Information Act 2011 and Press Freedom: Challenges and Prospects for Media Practice in Nigeria - Senam, Nsikan; Akpan, Uwem Udo; Mboho, Mbuk (International Journal of Emerging Trends in Social Sciences, 2017)
Information flow is not just a fundamental ingredient of democracy but also a sine qua none to the overall development of the society. Journalism plays an important role in ensuring that relevant information of significance is gathered, processed and transmitted to the citizenry. This paper hinged on access to and transmission of information. Specifically, it examined the Freedom of Information Act, 2011 and press freedom vis-a-vis their implications for journalism practice in Nigeria. The paper is a product of descriptive research and document analysis. Findings revealed that Nigeria’s Freedom of Information Act was not enacted exclusively to aid journalism practice, rather for use by the generality of Nigerians. However, if the applicable aspect of Act is properly harnessed by journalists, the contents of Nigerian mass media would be enriched. It is therefore recommended that the Nigerian Press Council should sponsor a bill in the National Assembly for the enactment of Journalism Practice Act in order to enhance professionalism and efficiency in journalism practice. Again, Nigerian journalists should not over-rely on the assurances of the Act as they are nothing far from façade, rather journalists should keep engaging in investigative journalism so as to publish the real truth not what public officers call the truth.